Effect of Core Material Thickness on the Shore Hardness of the Sandwich-Structured Multi-Material 3D-Printed Parts - Adib, Adam Zuyyinal; Mahardika, Muslim; Suyitno, Suyitno; Arifvianto, Budi; Pratama, Juan; Salim, Urip Agus (Applied mechanics and materials, 2024)
Fused Filament Fabrication (FFF) continues to experience improvements in terms of its flexibility and functionality, therefore it attracts public attention to use this technology. Multi-Material Additive Manufacturing (MMAM) is an approach in the FFF technology that allows the manufacturing of 3D-printed products composed of two or more materials in a single printing process. MMAM enables the user to apply various configurations to obtain a 3D-printed material with adjustable properties. This study aims to determine the effect of core material on the Shore hardness of the FFF printed parts with the MMAM approach. There were two types of materials combined with the MMAM approach in this work, namely polylactic-acid (PLA) and thermoplastic elastomer (TPE). The Shore hardness test was conducted according to the ASTM D2240-15 standard. The results showed that the thickness of the core material inserted into the printed material had a significant effect on the hardness value of printed multi-material parts. In addition, the hardness value was highly dependent on the modulus of elasticity of the material. Therefore, the hardness value changed following the proportion of the printed material.